2020
DOI: 10.3390/plants9111494
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Nodule-Associated Non-Rhizobial Bacteria Inhibit Plant Pathogens and Induce Growth Promotion in Tomato

Abstract: The root nodules are a unique environment formed on legume roots through a highly specific symbiotic relationship between leguminous plants and nodule-inducing bacteria. Previously, Rhizobia were presumed to be the only group of bacteria residing within nodules. However, recent studies discovered diverse groups of bacteria within the legume nodules. In this report soybean nodule-associated bacteria were studied in an effort to identify beneficial bacteria for plant disease control and growth promotion. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…No reuse allowed without permission. (13,59,60). We found that Pseudomonas ASVs were characteristic of healthy, but not of starved L. burttii nodules (Figure 5) suggesting they have the potential to support plant health.…”
Section: Pseudomonas Asvs Are More Prevalent In Healthy Plant Nodulesmentioning
confidence: 87%
“…No reuse allowed without permission. (13,59,60). We found that Pseudomonas ASVs were characteristic of healthy, but not of starved L. burttii nodules (Figure 5) suggesting they have the potential to support plant health.…”
Section: Pseudomonas Asvs Are More Prevalent In Healthy Plant Nodulesmentioning
confidence: 87%
“…Although it carries a large amount of PGP genes, O. muellerharveyae TH2 T showed no effect on sainfoin plants in our inoculation experiment under nitrogen-limited conditions. O nobrychidicola muellerharveyae TH2 T might achieve better potential under biotic stress condition [9], as its highest number of genes were found in functional classes referring to bacterial fitness/ stress tolerance. In contrast to most other Rhizobiaceae , which have only one copy, O. muellerharveyae TH2 T had four copies of the tabtoxin degradation gene ( ttr ).…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in different biological activities e.g. plant growth-promotion and biocontrol [9]. Nevertheless, our knowledge about the entire biological functions of nodule-associated bacteria is elusive.…”
Section: Introductionmentioning
confidence: 99%
“…NREs may also suppress plant pathogens. Tokgöz et al (2020) found that NREs isolated from soybean nodules have antifungal and antibacterial properties that extend beyond the nodule and interact with non-legumes. The authors found that an isolate of the genus Proteus was effective in inhibiting the growth of several bacterial and fungal pathogens in vitro.…”
Section: Contribution Of Nres To Legume Growth and Performancementioning
confidence: 99%